Biological assets as mudharabah-based loan collateral for smallholder farmers in Indonesia: a feasibility study - Sugiharto Soeleman; Gita Fitria (Diponegoro International Journal of Business, 2020)
Lack source of fund is one of the critical issues being faced by smallholder farmers. Despite having teak trees in their yards, such trees as biological assets are not accepted as loan collateral for bank's loan. In average, smallholder farmers fulfil their daily needs by cutting down their teak trees of five years old for sale. This research explored the feasibility of postponing teak harvesting time and analyzed the financial impact. By postponing the harvesting time, it is expected that the growth of the diameter and height of the tree, thus increasing the volume, and the price increases will increase the value of the asset. The method being employed was enterprise budget in which the costs of maintenance, the growth of the trees, and the sales of the harvested trees over time were considered. For the valuation, a profit-sharing as a result of value increases due to harvesting delay is shared between the owner of the asset and the investor through mudharabah financing arrangement. The result suggests that the annual return for the investor (such as a bank) is well above the current interest on a loan, and, therefore, biological assets should be justified as collateral for a bank loan.